Multianalyte nano-biosensor diagnostics: advances through microfluidic and AI integration - Pathak, Shashikant; Bazazordeh, Shadi; Çamlıca, Buse; Tzouvadaki, Ioulia (Frontiers in Bioengineering and Biotechnology, 2026)
Recent advances in nano-biosensors are reshaping clinical diagnostics by enabling multiplexed biomarker detection with high sensitivity and precision. This mini-review examines both the opportunities and challenges in translating nano-biosensor technologies toward clinically relevant point-of-care (PoC) and wearable devices. We emphasize the integration of multiplexing strategies with microfluidic platforms and adaptive artificial intelligence (AI) algorithms, which together enable real-time, high-throughput, and personalized health monitoring. Electrochemical and optical transduction approaches for multi-biomarker diagnostics are discussed, along with the role of microfluidic integration in enhancing sensor performance through precise sample processing, reduced reagent use, and simultaneous biomarker detection. A comparative overview of multiplexing approaches, including spatial, spectral, and temporal encoding is presented, with particular attention to sensor surface regeneration for device reusability. Furthermore, we explore the role of adaptive AI algorithms in individualising diagnostics to diverse patient groups while addressing key ethical and regulatory considerations such as algorithm transparency, patient data protection, and compliance with evolving medical device standards. By drawing together insights across nano-biosensor design, microfluidics, and AI, this mini review provides practical guidance for advancing next-generation diagnostic platforms toward clinical translation.